Frames, schemata, and news reporting - Scheufele, Bertram (comm, 2006)
Abstract This article deals with frames and schemata in news reporting. It distinguishes frames and schemata in newsroom discourse and news reports. On the individual cognitive level, a frame is defined as a set of schemata for different aspects of reality. They emerge in newsroom discourse and in exchange with other (media) discourses, i. e., they are not idiosyncratic but shared among those working in a newsroom. It is supposed that news report structures (media frames) correspond to these newsroom frames and schemata. The article discusses these considerations in regard to related explanations of news production, especially attitudinal approaches such as news bias. While the latter assume that journalists prefer information consistent with their own attitudes or that news reporting is ‘synchronized’ with editorial tendencies, the framing approach proposes that information in routine news reports correspond to newsroom frames. In this study I will use xenophobia as an example to identify newsroom frames in a qualitative frame analysis. In the second part of the study, quantitative analysis of news framing examines whether news report information correlates with newsroom frames. Finally, I will present empirical evidence that shows that newsroom frames play a role in news reporting.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTUxNS9jb21tdW4uMjAwNi4wMDU